Perancangan Aplikasi Penilaian Tingkat Kesehatan Bank Umum Menggunakan Metode Risk Based Bank Rating - Maulana Harun Ar-rosyyid; Destian Arshad Darulmalshah Tamara; Rosma Pakpahan (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
The soundness level of a bank is a qualitative assessment of various aspects that affect the condition or performance of a bank through quantitative or quantitative assessments. In this Regulation of the Financial Services Authority Number 4 / POJK.03 / 2016 using an individual and consolidated risk approach (Risk Based Bank Rating / RBBR). This risk approach includes the Risk Profile, Good Corporate Governance, Earnings and Capital factors. Conducting an assessment is not easy, especially if it is still manual for the process. That way designing an application is the right way to solve it because it can simplify the work process by utilizing existing technology capabilities. Android-based technology is one of the most dominating technologies in use throughout the world. This study aims to design an application to process financial report data for the commercial bank sector into information on the health level of commercial banks based on the RBBR method and to present the development (comparison) of the soundness level of commercial banks in a two years period with the help of an android-based application. The design of this application uses a prototype approach method with several stages, namely identifying needs, making prototypes, testing prototypes, improving prototypes and developing production versions. Then the trial was carried out at one commercial bank for two consecutive periods at once. The test results on the application design for calculating the soundness level of a commercial bank based on the RBBR method in accordance with applicable regulations have been able to determine the composite rating (PK) and can suggest developments (comparisons) on the NPL, GCG, ROA and CAR factors in one commercial bank for two consecutive periods at once.